A numerical study on the bonding of the thin-walled and large-deformation composite components. Issue 17 (2nd September 2021) - Deng, Qian; Qi, Junwei; Wang, Yuequan; Shi, Jiaqi; Li, Xiaoping
Abstract: Thin-walled and large-deformation composite components that need to be stowed and deployed as space deployable structures require a high bonding property. The purpose of this work is to study the failure mode and influence of scroll radius, adhesive elastic modulus, adhesive thickness, and layup angle on the stress of the adhesive layer and strain energy through a numerical method. A good agreement between experimental and numerical results was obtained verifying the numerical method. Firstly, results show that as the scroll radius increases, the shear and peel stress of the adhesive layer, as well as the strain energy, decrease and the failure of the adhesive layer is mainly peel failure. Furthermore, in addition to the shear and peel stress, the strain energy is also substantially affected by the ply angle. Considering the shear stress, peel stress, and strain energy, the [90/0]s ply becomes the best choice. The shear and peel stress increase with increasing adhesive elastic modulus. Lastly, an increase in adhesive thickness is found to decrease the shear and peel stress of the adhesive layer. However, the change in strain energy corresponding to the change in adhesive thickness is small. This study paves the way for the selection of bonding parameters of thin-walled and large-deformation composite components.